Highly diverse cembranoids from the South China Sea soft coral Sinularia scabra as a new class of potential immunosuppressive agents. Issue 15 (1st August 2019) - Yang, Min; Li, Heng; Zhang, Quan; Wu, Qi-Hao; Li, Geng; Chen, Kai-Xian; Guo, Yue-Wei; Tang, Wei; Li, Xu-Wen
Graphical abstract: Abstract: The first and in-depth chemical investigation of the South China Sea soft coral Sinularia scabra has resulted to the isolation of a library of diverse cembrane type diterpenoids, including six new compounds, namely xiguscabrates A and B (1 and2 ), xiguscabral A (3 ), xiguscabrols A and B (4 and5 ), and 8- epi -xiguscabrol B (6 ), and twenty-seven known analogs (7 –33 ). Their structures were elucidated by extensive spectroscopic analysis and by the comparison with literature data. In bioassay, several isolates exhibited inhibitory effects on the ConA-induced T lymphocytes and/or LPS-induced B lymphocytes proliferation. Among them, compound24 showed considerable specific inhibition on B cell proliferation, with IC50 value of 4.4 μ M and selectivity index (SI) of 10.9. The structure-activity relationship (SAR) of the tested metabolites was analyzed, and the further mechanism study of the specific B-cell targeted immunosuppressive compound24 on purified CD19 + B cells was also performed to uncover the effects on the function and maturity of B cells, including cytokines production, abnormal activation, antigen presenting capacity and plasma cells formation.